2020
DOI: 10.1001/jamaophthalmol.2020.2254
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Racial, Ethnic, and Socioeconomic Associations With Treatment and Survival in Uveal Melanoma, 2004-2014

Abstract: Identifying disparities in uveal melanoma (UM) treatment patterns and survival across racial, ethnic, and socioeconomic (SES) groups reveals possible inequities in ophthalmologic health care.OBJECTIVE To examine the association of race, ethnicity, and SES with UM treatment and survival. DESIGN, SETTING, AND PARTICIPANTSA retrospective cohort analysis of 28% of the US population using the Surveillance, Epidemiology, and End Results (SEER) 18 registries from January 1, 2004, to December 31, 2014, was conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 51 publications
3
40
0
Order By: Relevance
“…Although new techniques such as proton beam therapy have been introduced (5), plaque brachytherapy, mainly using iodine-125, remains the dominant option as an eyeball-conserving treatment for UM. In the United States, the ratio of plaque brachytherapy is increasing each year, which accounts for more than 50% recently (6,7). The same case was also seen in our eye center.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Although new techniques such as proton beam therapy have been introduced (5), plaque brachytherapy, mainly using iodine-125, remains the dominant option as an eyeball-conserving treatment for UM. In the United States, the ratio of plaque brachytherapy is increasing each year, which accounts for more than 50% recently (6,7). The same case was also seen in our eye center.…”
Section: Introductionsupporting
confidence: 76%
“…Patients who were diagnosed with UM at the Beijing Tongren Eye Center and subsequently received brachytherapy were included in this study. The exclusion criteria were: (1) age<18 years, (2) received other therapies, (3) alive and had a follow-up time of fewer than 4 years, (4) the third follow-up time was more than 3 years, (5) filled follow-up time was later than the time of outcome, (6) had metastatic disease at the time of diagnosis. Finally, 454 patients were included to construct the model for predicting death and 424 patients to build the model for predicting metastasis (Figure 2A).…”
Section: Selection Of Participantsmentioning
confidence: 99%
“…Rajeshuni et al made evaluation of socioeconomic associations with treatment and survival in UM. The results showed that socioeconomically disadvantaged patients with UM are more likely to be treated with primary enucleation and also revealed opportunities to address issues regarding treatment choice in UM, which was a merit point in this work [ 36 ]. However, no study has emphasized the influence of marital status on UM patients or has conducted subgroup analysis stratified by sex and SEER stage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that race and SES affect overall and disease-specific mortality for cancer in general, so we hypothesized that race, ethnicity, and SES would similarly impact the DSS and CDSS of NPC . 13 14 15 16 Findings from this study could help to identify potentially modifiable variables that determine survival and prognosis for NPC.…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have illustrated the validity of the Yost Index in cancer-related outcomes. 13 14 15 16…”
Section: Introductionmentioning
confidence: 99%